Development of a novel electric field-assisted modified hydrodynamic cavitation system for disintegration of waste activated sludge - Jung, Kyung-Won; Hwang, Min-Jin; Yun, Yeo-Myeong; Cha, Min-Jung; Ahn, Kyu-Hong (ELSEVIER SCIENCE BV, 2014)
In this current study, we present a modified hydrodynamic cavitation device that combines an electric field to substitute for the chemical addition. A modified HC system is basically an orifice plate and crisscross pipe assembly, in which the crisscross pipe imparts some turbulence, which creates collision events. This study shows that for maximizing disintegration, combining HC system, which called electric field-assisted modified orifice plate hydrodynamic cavitation (EFM-HC) in this study, with an electric field is important. Various HC systems were compared in terms of disintegration of WAS, and, among them, the EFM-HC system exhibited the best performance with the highest disintegration efficiency of 47.0 +/- 2.0% as well as the destruction of WAS morphological characteristics. The experimental results clearly show that a conventional HC system was successfully modified. In addition, electric field has a great potential for efficient disintegration of WAS for as a additional option in a combination treatment. This study suggests continued research in this field may lead to an appropriate design for commercial use. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: WATER TREATMENT PLANTS; ANAEROBIC-DIGESTION; METHANE PRODUCTION; PRETREATMENT; SOLUBILIZATION; OZONATION; REMOVAL; ACIDIFICATION; HYDROLYSIS; REACTORS